2002
DOI: 10.1289/ehp.02110s5797
|View full text |Cite
|
Sign up to set email alerts
|

Interference by toxic metal ions with DNA repair processes and cell cycle control: molecular mechanisms.

Abstract: Nickel, cadmium, cobalt, and arsenic compounds are well-known carcinogens to humans and experimental animals. Even though their DNA-damaging potentials are rather weak, they interfere with the nucleotide and base excision repair at low, noncytotoxic concentrations. For example, both water-soluble Ni(II) and particulate black NiO greatly reduced the repair of DNA adducts induced by benzo[a]pyrene, an important environmental pollutant. Furthermore, Ni(II), As(III), and Co(II) interfered with cell cycle progressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
133
0
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 258 publications
(137 citation statements)
references
References 31 publications
(29 reference statements)
2
133
0
2
Order By: Relevance
“…30 Third, several studies done in vitro have shown plausible pathways such as increased oxidative stress, 29 modified activity of transcription factors, 31 and inhibition of DNA repair. 32,33 However, the role of these pathways in the response to toxic-metal exposure has not been defined in human beings.…”
Section: Discussionmentioning
confidence: 99%
“…30 Third, several studies done in vitro have shown plausible pathways such as increased oxidative stress, 29 modified activity of transcription factors, 31 and inhibition of DNA repair. 32,33 However, the role of these pathways in the response to toxic-metal exposure has not been defined in human beings.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that environmental metals are co-mutagenic by inhibiting DNA repair (45,46). Since WRN is suggested to have a role in DNA repair and replication, we sought to evaluate the effects of metal ions on WRN by examining WRN helicase activity in the presence of various metals at low micromolar concentrations in reactions that also contained a physiological concentration of Mg 2ϩ (1 mM).…”
Section: Optimal Atp-mg 2ϩ Concentration For Wrn Helicasementioning
confidence: 99%
“…Arsenic-induced oxidative stress can be attenuated, however, by modulation of cellular thiols [Flora, 2011]. Arsenite has been shown to inhibit poly(ADP-ribose) polymerase-1 (PARP-1), a major enzyme involved in DNA base excision repair by excising 8-hydroxyyl-2 0 -deoxyguanosine (8-OHdG) DNA lesions Wiencke, 1993, 1997;Hartwig et al, 2002;Qin et al, 2008;Zhou et al, 2011]. At exposures 3lM for 24 hr to As III alone in a human keratinocyte cell line (HaCat), no significant increase of ROS or DNA strand breaks was observed and PARP-1 activity was not detected [Qin et al, 2008].…”
Section: Introductionmentioning
confidence: 99%